CONTROL SHUNT ACTIVE FILTER BASED ON DQ FRAME USING CURRENT MODEL PREDICTION - Chí, Nguy?n V?n (International Journal of Applied Power Engineering (IJAPE))
The nonlinear loads present more in the power systems in the practice today by developing of electronic technology and using the small distributed power sources (solar power, wind power etc.?), this causes the increasing the high frequency switch devices etc. in the power network. Nonlinear loads cause non-sinusoidal currents and voltages with harmonic components, increasing the reactive power, overload of power lines and electrical devices, low power factor and affecting badly to the networks. Shunt active filters (SAF) with current controlled voltage source inverters (CCVSI) are used effectively to reduce the harmonics and to balance the phases sinusoidal source currents by generating the currents to compensate the harmonic currents caused by the nonlinear loads.  In this paper we suppose a control strategy to generate the compensation currents of SAF by using the current model predictive engineering. This method is better than the control strategy using PI controller in term of transient time. The desired compensation currents can track exactly the reference compensation currents on the dq frame. The simulation results implemented on the nonlinear load, a full bridge rectifier and 3 phase unbalance load, show that the transient period decrease from 0.1s to 0.02s in comparing with PI controller. The experimental results proof that the THD of source currents decrease from 24.8% to 5.4% when using the proposed method.